2019
DOI: 10.3390/ijerph16224512
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Disaster Risk Perception Process Model for Rural Households: A Pilot Study from Southwestern China

Abstract: There are many important factors to consider when creating robust, regional disaster prevention systems. These include rural households’ knowledge and reported skills of earthquake disasters, disaster risk perception, awareness of disaster risk reduction, willingness to purchase insurance, and willingness to relocate to avoid disasters. However, few empirical studies have systematically established the theoretical research frameworks to analyze these factors. This study analyzed the data sampled from 241 rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…So, flood risk knowledge is possibly a potential factor influencing individuals' attitudes towards floods (H4). According to Xu et al [26], disaster risk perception is found to be significantly positively correlated with coping behaviors to avoid disasters. At the same time, considering the important role of flood risk perception in flood risk management, we expect a higher risk perception to be directly related to more positive coping behaviors (H5).…”
Section: Methodsmentioning
confidence: 99%
“…So, flood risk knowledge is possibly a potential factor influencing individuals' attitudes towards floods (H4). According to Xu et al [26], disaster risk perception is found to be significantly positively correlated with coping behaviors to avoid disasters. At the same time, considering the important role of flood risk perception in flood risk management, we expect a higher risk perception to be directly related to more positive coping behaviors (H5).…”
Section: Methodsmentioning
confidence: 99%
“…According to statistics, since 2000, the earthquake caused a total of 87,900 people died, 830,400 people production and life seriously affected (CRED 2019). China frequently experiences earthquakes, many of which are extremely damaging (Xu et al 2015(Xu et al , 2019b. Since 2000, there have been 178 earthquakes in China greater than magnitude 5, causing a reported 486,000 casualties and direct economic losses of 111 trillion Yuan (CNSB 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, with the movement of geological plates, earthquake disasters have occurred frequently around the world, causing serious losses to human life and property [1][2][3][4]. Statistics indicate that between 2000 and 2018, 830,400 people were affected and 87,900 people were killed by earthquake disasters worldwide [5].…”
Section: Introductionmentioning
confidence: 99%